2022
DOI: 10.1111/aor.14321
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes for patients with bleeding complications receiving extracorporeal membrane oxygenation: An analysis of the Chinese Extracorporeal Life Support Registry

Abstract: Objective Bleeding is a severe complication of patients supported with extracorporeal membrane oxygenation (ECMO). This study aimed to analyze the occurrence, risk factors, and clinical outcomes of patients on ECMO with bleeding complications. Methods ECMO cases reported to the multicenter ECMO registry database of the Chinese Society of Extracorporeal Life Support (CSECLS) from January 2017 to December 2020 were enrolled. General information, ECMO indications, application, complications, and patient outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
3
15
2
Order By: Relevance
“…Major bleeding increased in-hospital morbidity but was not associated with increased mortality. The lack of association with in-hospital mortality diverges from some published ECMO studies where bleeding has been associated with increased mortality (9,21,28). In contrast to our data these studies included veno-venous and veno-arterial ECMO support (9,21,28) and pediatric and adult patients (9,21).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Major bleeding increased in-hospital morbidity but was not associated with increased mortality. The lack of association with in-hospital mortality diverges from some published ECMO studies where bleeding has been associated with increased mortality (9,21,28). In contrast to our data these studies included veno-venous and veno-arterial ECMO support (9,21,28) and pediatric and adult patients (9,21).…”
Section: Discussioncontrasting
confidence: 96%
“…For those patients who survived to extubation, the length of mechanical ventilation was longer in patients who had a major bleeding event (9 vs 6 days, p=0.05). The median length of hospital stay was 8 (2,21) days. Having a bleeding event was associated with a longer length of hospitalization with a median of 10(3,22) compared to 4(2,14) (p=0.01)days of admission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, ECMO remains a high-risk therapy with numerous known complications such as bleeding, thrombosis, and infection. [7][8][9][10] Further, disability after ICU stay and long-term mechanical ventilation is frequent with a substantial number of patients needing prolonged hospital stay and rehabilitation. [11][12][13] Early physiotherapeutic interventions and rehabilitation have been implemented to improve outcomes for ECMO candidates [14][15][16][17][18] ; however, careful patient selection is crucial to ensure favorable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a proportion of patients with accompanying cerebral infarction did not fully recover. A recent study has suggested that 18.1% of pediatric patients with ECMO experience hemorrhagic complications, including intracranial hemorrhage and thrombotic complications ( 20 ). We found that communication and motor dysfunctions persisted in patients after discharge.…”
Section: Discussionmentioning
confidence: 99%